Coinheritance of hemoglobin D-Punjab and β0-thalassemia 3.4 kb deletion in a Thai girl - Sitthichai Panyasai (2018)
© 2017 Asian Journal of Transfusion Science. Hemoglobin (Hb) D-Punjab [β 121(GH4) Glu→ln; HBB: C.364G>C] and β0-thalassemia 3.4 kb deletion are very rare in the Thai population. For the first time, the coinheritance of HbD-Punjab with β0-thalassemia 3.4 kb deletion was reported in a 7-year-old Thai girl. She had mild anemia (Hb 115.0 g/L and mean corpuscular hemoglobin 18.1 pg) with red blood cell microcytosis (mean corpuscular volume 52.5 fL). By capillary electrophoresis (CE), HbD-Punjab was found at a migration position of 180 s with the value of 81.9% while the level of HbA2was 7.3%. Based on the elevated HbA2, the molecular analysis for detection of β0-thalassemia mutations was performed. The 490 bp amplified fragments from β0-thalassemia 3.4 kb deletion was observed. Thus, the coinheritance of HbD-Punjab with β0-thalassemia can be found in the Thai population. The HbA2measured on CE is a reliable parameter for differentiating the homozygote of HbD-Punjab and compound heterozygote of HbD-Punjab and β0-thalassemia.